Contemporary issues in finance current challenges from across Europe - Bezzina, Frank; RomaU+0304‰nova, Inna; Rupeika-Apoga, Ramona; Grima, Simon (Contemporary studies in economic and financial analysis ;, 2016)
Including studies on different topical issues in finance by the participants of the 8th international scientific conference "New Challenges of Economic and Business Development - 2016" this new work contains research from various European countries, specifically Germany, Italy, Latvia, Malta, and Poland. Chapters explore the impact of financial literacy on domestic economic activity in the Baltic States, the rapid rise of FinTech, which has changed the banking landscape, requiring more innovative solutions; Crowdfunding in the European Union, specifically examining the performance, development and perspectives; the case of Latvia to highlight the Profiles of SMEs as Borrowers, the factors that interfere with the availability of funding to the small and medium-sized companies, an analysis of Risk Parity Approach for Sovereign Fixed-Income Portfolios in Eurozone countries by looking at studies of preventive arrangements with creditors in Italy; and Mergers and Acquisitions by studying examples of best practices in Cross-Border acquisitions.